Stepping Out of the Shade: Control of Neuronal Activity by the Scaffold Protein Kidins220/ARMS - Scholz-Starke, Joachim; Cesca, Fabrizia (Frontiers in Cellular Neuroscience, 2016)
The correct functioning of the nervous system depends on the exquisitely fine control of neuronal excitability and synaptic plasticity, which relies on an intricate network of protein-protein interactions and signaling that shapes neuronal homeostasis during development and in adulthood. In this complex scenario, Kinase D interacting substrate of 220 kDa / ankyrin repeat-rich membrane spanning (Kidins220/ARMS) is a multi-functional scaffold protein preferentially expressed in the nervous system. Engaged in a plethora of interactions with membrane receptors, cytosolic signaling components and cytoskeletal proteins, Kidins220/ARMS is implicated in numerous cellular functions including neuronal survival, neurite outgrowth and maturation and neuronal activity, often in the context of neurotrophin signaling pathways. Recent studies have highlighted a number of cell- and context-specific roles for this protein in the control of synaptic transmission and neuronal excitability, which are at present far from being completely understood. In addition, some evidence has began to emerge, linking alterations of Kidins220 expression to the onset of various neurodegenerative diseases and neuropsychiatric disorders. In this review, we present a concise summary of our fragmentary knowledge of Kidins220/ARMS biological functions, focusing on the mechanism(s) by which it controls various aspects of neuronal activity. We have tried, where possible, to discuss the available evidence in the wider context of neurotrophin-mediated regulation, and to outline emerging roles of Kidins220/ARMS in human pathologies.